Planning and Procurement of the Blood Enhancing Tablet Program for Adolescent Girls in Indonesia with a Systematic Review - Fajarini, Dessy; Adlia Syakurah, Rizma; Idris, Haerawati (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Anemia in adolescent girls remains a public health problem in Indonesia, while the Iron Supplement (TTD) program has not been running optimally due to constraints in planning, procurement, and distribution. Systematically reviewing the scientific evidence related to the planning and procurement of TTD for adolescent girls in Indonesia. Methods: This study used a systematic review method based on the PRISMA guidelines. Article searches were conducted through PubMed, Google Scholar, ScienceDirect, DOAJ, and Garuda during the period 2020–2025. Of the 212 articles found, 15 met the inclusion criteria and were analyzed using a narrative approach based on the following themes: program planning, distribution, and compliance. Results : The study results show that the planning and procurement of iron tablets remains inaccurate, distribution is inconsistent, and adolescent girls' compliance with iron tablets remains low. Inhibiting factors include budget delays, weak cross-sectoral coordination, a lack of regional regulations, and minimal education and environmental support. Innovations through teacher empowerment and the use of digital media have been shown to improve knowledge and compliance. Conclusion: Improved data-driven planning, optimized logistics distribution, and innovative educational strategies are needed to increase the effectiveness of the TTD program in reducing the prevalence of anemia among adolescent girls in Indonesia.